Comparative thermal analysis of extruded ceramic products between multi perforated brick and modified bricks in cells distribution (2019)
The demand for cooling and heating systems to adapt spaces is a critical environmental problem due to the high energy consumption required for its operation. For this reason, the offer of products for architectural facades should consider constructive solutions that mitigate the heating of buildings. Thermal behavior of building materials is an elementary factor in the energy consumption of buildings. This paper presents the comparative thermal analysis of 4 ceramic product designs for masonry, of which, one represents the traditional multi perforated brick and the others, are proposed to prove whether shape affects the heat transfer processes. The research methodology is divided into 2 stages: product design and thermal validation by transfer and heat fluxes in the ANSYS R16 software using the finite element method. For the design process, modification of the internal cells and elimination of the thermal bridge was implemented. Simulations were configured under the highest values of solar radiation recorded in the city of San José de Cúcuta, Colombia to know the products performance in the most extreme conditions of the city. The results indicate that design varies energy performance of the product, since it reduces the temperature of the inner surface to 1.23 °C or increase it to 2.25 °C. The results show that the modification of cells distribution and elimination of thermal bridges are passive strategies for the reduction of heat transfer in the design of ceramic product for masonry. This research is a breakthrough for future research that develops constructive units focused on improving the quality of life of people from thermal comfort, energy efficiency and the use of local resources and technologies.